#### Answer

$-2a^7y^2$

#### Work Step by Step

$\sqrt[3] {-8a^{21}y^6}=-2a^7y^2$
because,
$(-2a^7y^2)^3=-8a^{21}y^6$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-2a^7y^2$

$\sqrt[3] {-8a^{21}y^6}=-2a^7y^2$
because,
$(-2a^7y^2)^3=-8a^{21}y^6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.